POSSIBILITIES OF ENDOSCOPIC STUDIES IN THE DIAGNOSIS OF ABDOMINAL TUBERCULOSIS (Conferencea, 2021)
Extrapulmonary tuberculosis (BT), in comparison with pulmonary tuberculosis, is, as it were, inthe shadows due to low epidemiological indicators. In 1999, in Russia, the ratio of persons with pulmonaryand extrapulmonary tuberculosis who were registered at the dispensary was 12: 1. In highly developedcountries, HT is 20-40% in the overall structure of tuberculosis morbidity. In developed countries (Canada),the main risk groups for BT are aborigines, immigrants from regions endemic for BT, and HIV-infectedpatients. In developing countries with a high level of HIV infection in the population, there is a highlikelihood of a change in BT symptoms in case of mixed infection with both pathogens